Do trade and foreign direct investment contribute to growth? A study of BIMSTEC nations - Vandana Arya; Ravinder Verma; Vijender Pal Saini (Journal of Business and Socio-Economic Development)
Purpose – The study examines the association between trade (exports and imports), foreign direct investment (FDI) and economic growth in the Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC) countries using data from 1991 to 2019. Design/methodology/approach – Augmented Dickey–Fuller (ADF) and Phillips–Perron (PP) unit root tests were applied to check the stationary of the data while the Johansen cointegration test and Vector Error Correction Model (VECM) was used to analyze long-run and short-run relationships. Findings – The results indicate a long-run relationship between trade, FDI and economic growth in all selected countries except Bhutan. Additionally, a bidirectional causality exists between gross domestic product (GDP) and FDI in India, Bangladesh, Myanmar, Nepal, Bhutan and Sri Lanka, while unidirectional causality from GDP to FDI is observed in Thailand. Moreover, a one-way causality from exports to GDP exists in Bangladesh, Nepal, Bhutan, Sri Lanka and Myanmar, whereas a bidirectional relationship exists in India and Thailand. Practical implications – This paper will be highly beneficial for regulators and policymakers in the designated economies, aiding in the formulation of FDI and trade policies that promote economic progress and development. Originality/value – Most previous studies examining the relationship between macroeconomic variables have focused on developed nations. This study is the first to explore the relationship between trade (exports and imports), FDI and economic growth in the BIMSTEC countries.